PENGARUH FINANCIAL DISTRESS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Consumer Non Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Sari, Diah Ayu Herdita; Rosyati, Tati (Worksheet : Jurnal Akuntansi, 2025)
This study airms to test and obtain empirical evidence regarding the effect of financial distress and institusional ownership on tax avoidance with company size as a moderating variable. The research sample consists of companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange during the 2018–2023 period. The data used are financial reports. Sampling techniques used in this researchis purposive sampling method and data analysis is conducted using E-Views 12. This research adopts a quantitative approach, involving 33 companies observed over five years, resulting in a total of 165 data points. The analytical method used is panel data regression. The results of this study indicate that simultaneously, financial distress and institutional ownership have an effect against tax avoidance. Partially, financial distress has a negative and significant impact on tax avoidance, while institutional ownership shows no partial effect on tax avoidance. The results obtained show that company size cannot moderate the influence of financial distress and institutional ownership on tax avoidance.